2005
DOI: 10.1182/blood-2005-01-0050
|View full text |Cite
|
Sign up to set email alerts
|

Low Mpl receptor expression in a pedigree with familial platelet disorder with predisposition to acute myelogenous leukemia and a novel AML1 mutation

Abstract: Germ-line heterozygous mutations in the hematopoietic transcription factor AML1 (RUNX1) have been identified in patients with familial platelet disorder with predisposition to acute myelogenous leukemia (FPD/AML), which is characterized by thrombocytopenia, abnormal platelet function, and propensity to myeloid malignancies. We identified a novel mutation in the AML1 gene in an FPD/AML pedigree characterized by a single nucleotide deletion that generates a frameshift and premature chain termination (Pro218fs-Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 35 publications
3
89
0
Order By: Relevance
“…Although the incidence is less common, the mutations in the C-terminal region have been reported [25]. In this case, the mutation generates a frameshift and premature chain termination, resulting in the lack of transactivation domain [25]. Intragenic deletions, which are not identified by traditional sequence analysis, have also been reported in a few families [9,26,27].…”
Section: Identification Of Runx1 Mutations As a Causative Genetic Evementioning
confidence: 98%
See 2 more Smart Citations
“…Although the incidence is less common, the mutations in the C-terminal region have been reported [25]. In this case, the mutation generates a frameshift and premature chain termination, resulting in the lack of transactivation domain [25]. Intragenic deletions, which are not identified by traditional sequence analysis, have also been reported in a few families [9,26,27].…”
Section: Identification Of Runx1 Mutations As a Causative Genetic Evementioning
confidence: 98%
“…The RUNX1 mutations identified in the individuals of FPD/AML pedigrees are generally located in the RHD, leading to disruption of DNA binding ability. Although the incidence is less common, the mutations in the C-terminal region have been reported [25]. In this case, the mutation generates a frameshift and premature chain termination, resulting in the lack of transactivation domain [25].…”
Section: Identification Of Runx1 Mutations As a Causative Genetic Evementioning
confidence: 99%
See 1 more Smart Citation
“…Germ line mutations of RUNX1, which cause monoallelic loss of RUNX1 complexes, are found in the autosomal dominant familial platelet disorder (FDP) with multiple platelet defects, reduced c-Mpl and predisposition to AML (Heller et al, 2005). Megakaryocytic and erythroid lineages, which are derived from a common bipotential progenitor, share many early lineage-restricted TFs (Shivdasani et al, 1997).…”
Section: Nuclear Transcription Factorsmentioning
confidence: 99%
“…So far, 13 pedigrees have been reported, mainly in European countries. [5][6][7][8][9][10] Clinically, the disorder is characterized by moderate thrombocytopenia from birth, impaired platelet function and a propensity to develop myeloid malignancies. Genetic and molecular studies reveal that all reported pedigrees of FPD/MM display a mutation in the RUNX1 gene or LOH at the locus.…”
mentioning
confidence: 99%